High-Efficiency Crossed-Loop 4G LTE Antenna for All Display Metal-Rimmed Smartphones - Jaehyun Choi; Woonbong Hwang; Chisang You; Byungwoon Jung; Wonbin Hong (International Journal of Antennas and Propagation)
A symmetrically crossed-loop antenna featuring very high radiation efficiency across the entire LTE frequency bands for metal-rimmed smartphones with only 2 mm ground clearance is proposed, analyzed, and verified. The employment of even and odd modes is utilized to achieve wide bandwidth across 698–960 MHz (low-frequency spectrum), 1710–2170 MHz (middle-frequency spectrum), and 2300–2690 MHz (high-frequency spectrum). Empirical analysis confirms the crossed-loop topology results in a 180° phase shift of the electric current distribution on the ground plane, resulting in enhancement of the radiation resistance. As a result, the devised LTE antenna exhibits more than 48% to 75% total system efficiency across the entire band of interest, which is the highest efficiency reported in literature for metal-rimmed smartphones with extremely small ground clearance.